Manajemen Pelaksanaan Pembelajaran TIK Pasca COVID-19 pada SD NEGERI 16 KOTA BANDA ACEH - Hazal Fitri; Sarniyati Yusmanita Dinas (LP3M KH Yazid Karimullah Institute, 2021)
The management of the implementation of post-covid-19 learning is interesting to study this, is one of the issues that became one of previous educational evaluation materials from online back to trailing. The use of ICT in the implementation of learning as a learning medium to facilitate the delivery of information or teaching materials. The purpose of this research is to know: 1) preparation of post-Covid-19 learning planning, 2) implementation of post-COVID-19 learning, 3) evaluation of learning in the use of ICT in the State SD 16 City of Banda Aceh post-covid-19. This research uses descriptive methods as well as qualitative approaches. The data collection techniques used are observations, interviews, and documentation studies. The subjects were two teachers, one head of school, one supervisor, and 96 students. Study results: 1) Learning Planning in the Use of Post Covid-19 ICTs in the State SD 16 Banda Aceh prepared by teachers based on the Merdeka curriculum with the guidance of the BSNP. Learning equipment in the use of ICTs is prepared only by the teachers of classes 4A, 5A and 6A in the field of mathematical studies, IPA, IPS, PAI and TIK. These devices have been handed over to the head of school at the beginning of each semester to be signed. 2) Learning should not all be carried out on the basis of planning due to media limitations, implementation time, while for exploration, elaboration and confirmation on such activities teachers always do absence, perception, motivate students and not forget to inform the purpose of learning. 3) Evaluations performed by teachers more frequently by evaluating the activity of students, the way they work and the results they work.